Low levels of progesterone and derivatives in cerebrospinal fluid of patients affected by status epilepticus. Issue 2 (30th August 2018) - Meletti, Stefano; Lucchi, Chiara; Monti, Giulia; Giovannini, Giada; Bedin, Roberta; Trenti, Tommaso; Rustichelli, Cecilia; Biagini, Giuseppe
Abstract : Some steroids directly produced into the brain act as anticonvulsants by positively modulating γ‐aminobutyric acid type A (GABAA ) receptor‐mediated inhibitory currents. We hypothesized that these 'neurosteroids' could be reduced in patients with status epilepticus (SE). Our findings show that all neurosteroids synthetized after conversion of pregnenolone to progesterone by 3β‐hydroxysteroid dehydrogenase are reduced in the cerebrospinal fluid of patients with SE. In particular, the reduction in progesterone, pregnanolone and allopregnanolone may play a role in the development of SE. Abstract: Neurosteroids such as allopregnanolone may play a role in epilepsy as positive modulators of inhibitory currents mediated by γ‐aminobutyric acid type A (GABAA ) receptor. Indeed, these molecules have been consistently shown to be anticonvulsants in animal models, but their role is still unclear in patients. For this reason, we investigated neurosteroids in the cerebrospinal fluid (CSF) of patients with status epilepticus (SE) by liquid chromatography tandem‐mass spectrometry. Patients were retrospectively identified within subjects who received a lumbar puncture in the 2007–2017 period. Seventy‐three patients (median age 65, ranging from 13 to 94 years; 67% women) with SE were evaluated. Controls ( n = 52, median age 53, ranging from 16 to 93 years; 65% women) were patients presenting with symptoms for which a lumbar puncture was required by clinical guidelines, and who were negative at the end of the diagnostic work‐up. Progesterone was 64% lower in patients with SE ( p < 0.001). With respect to progesterone, upstream pregnenolone sulfate and pregnenolone did not change. Instead, downstream 5α‐dihydroprogesterone, pregnanolone and allopregnanolone were, respectively, 49% ( p < 0.001), 21% ( p < 0.01) and 37% ( p < 0.001) lower than in controls. Duration or type of SE, age and sex did not consistently affect CSF neurosteroid levels in the SE cohort. Instead, pregnenolone sulfate (Spearman's ρ = 0.4335, p < 0.01), allopregnanolone (ρ = 0.4121, p < 0.05) and pregnanolone (ρ = 0.592, p < 0.001) levels significantly increased by aging in controls. We conclude that neurosteroidogenesis is defective in patients with SE.